Safe Online, Stronger Self: Psikoedukasi untuk Meningkatkan Self-Control sebagai Upaya Preventif Sextortion pada Remaja - Shinta Aprillia Pramesti; Djudiyah Djudiyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Adolescents are a vulnerable group to digital sexual violence, including sextortion, which involves sexual extortion through threats to distribute sexually explicit content. Low levels of self-control may increase adolescents’ vulnerability to such risks. This study aimed to examine the effectiveness of psychoeducation in enhancing self-control understanding as a preventive effort against sextortion among adolescents. A quantitative approach with a pre-experimental one-group pre-test–post-test design was employed. The participants consisted of 36 students aged 15–17 years from a public senior high school in Samarinda. The psychoeducational intervention was delivered through interactive lectures, Focus Group Discussions (FGD), and educational video screenings. Data were analyzed using the Wilcoxon Signed-Rank Test. The results of the analysis showed a statistically significant difference (Z = −2.201; p = 0.028 (p < 0.05)). This indicates that there was a difference in adolescents’ self-control before and after the psychoeducation intervention. The post-test mean score (M = 8.39) was higher than the pre-test mean score (M = 8.00). These findings suggest that psychoeducation was effective in improving adolescents’ understanding of self-control as a preventive effort against sextortion. Self-control psychoeducation can therefore be considered a relevant preventive approach to be implemented in school settings.